The Effect of Application of Restaurant Laboratory Management System on College Student Service Satisfaction At The Department of Home Economic Education Faculty of Engineering, Universitas Negeri Surabaya - Yuliana, Siti; Nurlaela, Luthfiyah; Handajani, Sri; Rijanto, Tri (International Journal for Educational and Vocational Studies, 2020)
The study was aimed to obtain information the effects the application of system the management of lab where internal conditions a restaurant of the results of the learning and of the level of satisfaction study on public service delivery a student on the directions in which their four of family welfare education of engineering faculty Universitas Negeri Surabaya. The results of the hypothesis in this research showing no influence between management systems laboratory restaurant to study results , especially in study results domain cognitive and domain affective students p of culinary of education family welfare Universitas Negeri Surabaya , but results test hypothesis said influential application of the system laboratory management to study results psychomotor domain .The results of the hypothesis said that there was no influence management systems laboratory to satisfaction service .The results of the hypothesis showing no influence between management systems laboratory restaurant of the results of learning and satisfaction students  of culinary of education family welfare Universitas Negeri Surabaya. This research result in line with several theories that supports. Condition services not yet filled in the system this research that led to the absence of the influence of the application of the system of indicators service so an impact on indicators.